Mapping the Sectoral Innovation System of Iranian Automotive Industry - Ghasemipoursabet, Hamid (My University, 2025)
This thesis examines the sectoral innovation system (SIS) of Iran's automotive industry through a qualitative analysis of interactions among key actors, institutional frameworks, and market dynamics. Based on eight in-depth interviews with diverse stakeholders, the research identifies a distinctive "resilient but static innovation equilibrium" characterized by remarkable system persistence despite external constraints, alongside limited technological advancement. The study reveals three self-reinforcing mechanisms that maintain this equilibrium: the Institutional-Technological Lock-in Cycle, the Hierarchical Learning-Competency Trap, and the Market-Capability Constraint Loop. These mechanisms explain why, despite apparent incentives for transformation, the system prioritizes continuity over advancement. The research contributes to SIS theory by demonstrating how innovation systems in latecomer economies can develop stable patterns that diverge from traditional innovation trajectories, highlighting the critical importance of knowledge translation mechanisms across institutional boundaries, and suggesting a nuanced, non-linear relationship between protective policies and innovation capacity. The findings provide practical insights for policymakers, industry leaders, and research organizations seeking to enhance innovation within Iran's automotive sector while aligning with national development objectives.
Keywords: Sectoral Innovation System, Automotive Industry